Study of antioxidant activities in kacip fatimah (labisia pumila var alata) - Syazana Azman (2014)
Plants are one of the sources of medicine to treat many diseases and illness since long time ago. Many scientists began to extract and modify the active ingredients from plants that have led to the wide development of natural or traditional medicines since 19th century. Kacip Fatimah is one of the examples of traditional medicines that have been used by women and therefore it is called "queen of Malaysian herbs". This research emphasized the extraction of antioxidant in leaves of Labisia pumila var alata. The focus of the research are to study the presence of antioxidant activity in different part of leaves (young, medium and mature) by using free radical scavenging activity in DPPH assay and also to study the anthocyanin content of different part of leaves by using chloroform in fresh leaves. The methods used are DPPH assay and chloroform. Based on DPPH assay method, the result showed young leaves have the highest inhibition of antioxidant scavenging activity which was 87.76 %, 88.08 % and 87.66 % respectively in all three plants. Meanwhile in chloroform extraction, young leaves showed the highest anthocyanin content 1.66. The result showed antioxidant scavenging activity in young leaves were high in DPPH assay and the anthocyanin content in young leaves also high based on chloroform extraction.